Concept of Vidradhi WSR to abscess: an ayurvedic review - Gujjarwar, Shriniwas; Arya, Poonam (International Surgery Journal, 2021)
Ayurveda, a characteristic arrangement of medication, started in India over 3,000 years prior. The term Ayurveda is taken from the Sanskrit words ayur (life) and veda (science or information). In this manner, Ayurveda means information on life. In the wake of Collecting the information from various samhitas, ayurvedic texts and current books. Acharya sushruta- the father of Indian surgery has logically characterized in a foundational way an abundance of clinical material and the standards of the board for vidradhi, which are legitimate even today. "Sheegra vidhahivat'' meaning of vidradhi itself recommends the destructiveness of the disease. Vidradhi word is advanced from vidra, i.e, a painfull condition like pricking, stabbing or cutting sensation in the skin. The infection Vidradhi (abscess) is a typical infirmity disturbing mankind and debilitate the victim for his standard work. It presents as a limited expanding with torment, red discoloration,local rise of temperature, delicacy and confined capacity of impacted part. it is normal in India with second most noteworthy frequency because of helpless disinfection, stuffing and deficient sustenance. Around the world, roughly 40-50 million individuals are contaminated every year with amoebic abscesses. The current exploration article is intended for relative investigation of Vidradhi and Abscess as far as Samprapti (Pathophysiology), Lakshanas (Clinical elements) and Chikitsa (Treatment) affirms that Vidradhi and Abscess can be comparable disease entities.